Airbag associated fatal head injury: case report and review of the literature on airbag injuries. Issue 2 (1st March 2000) - Cunningham, K; Brown, T D; Gradwell, E; Nee, P A
Abstract : Airbags have been shown to significantly reduce mortality and morbidity in motor vehicle crashes. However, the airbag, like the seat belt, produces its own range of injuries. With the increasing use of airbags in the UK, airbag associated injuries will be seen more often. These are usually minor, but in certain circumstances severe and fatal injuries result. Such injuries have been described before in the medical literature, but hitherto most reports have been from North America. This is the first case report from the UK of serious injury due to airbag deployment and describes the case of a driver who was fatally injured when her airbag deployed in a moderate impact frontal collision where such severe injury would not normally have been anticipated. The range of airbag associated injuries is described and predisposing factors such as lack of seat belt usage, short stature, and proximity to airbag housing are discussed. The particular dangers airbags pose to children are also discussed.